Estimation of Sidelobe Level Variations of Phased Codes in Presence of Random Interference for Bistatic Wideband Noise Radar - Ana Vazquez Alejos; Muhammad Dawood; Habeeb Ur-Rahman Mohammed (International Journal of Antennas and Propagation)
We discuss the importance of using the sidelobe level of the cross-correlation function as a criterion to implement a noise radar based on the transmission of wideband binary waveforms. Theoretical expressions are introduced for the parameters Peak-Sidelobe, Secondary-Sidelobe, and Integrated-Sidelobe levels for both Golay and pseudorandom binary sequences in presence of additive white Gaussian noise, relating the sequence length M to the spectral power N0 of the interfering noise. These expressions offer a valuable method for adaptive radar waveform design in order to determine sequence requirements which allow facing the noise present in the frequency band of interest. We also show a comparison of the ambiguity functions for Golay and PRBS sequences to analyze their performance in terms of Doppler and range accuracy. We describe a practical implementation of a pseudonoise waveform-based bistatic radar with reduced sidelobe level due to the use of Golay codes in combination with single side band modulation and operation at UHF band. Experimental measurements were performed in actual scenarios for ranging test of single and double targets. Linear polarizations were combined with different length sequences to determine their influence on the sounder performance under field test conditions.